MODEL OF CLUSTER INITIATIVE IN EDUCATIONAL SYSTEM - RESEARCH ON EDUCATION IN CONJUNCTION WITH LABOUR MARKET - Agata Pradela (European Regional Science Association (ERSA), 2011)
Education for labour market on the school level is neglected in Poland. Concentration on university degree and general education caused the decrease of interest of vocational education of qualified workers (needed on labor market). To the most important problems in management in the area of vocational education belong: 1. Increasing number of lower secondary schools graduates choosing general secondary schools and willing to continue education at universities. 2. Decreasing interest of vocational education. 3. Lack of information of labour market requirements and very inefficient cooperation between labour market and educational system. 4. Graduates knowledge, qualifications, skills and attitudes does meet labour market needs. To solve these problems the Author suggests to create the cluster initiative in educational system (as a part of research of the project "Creation the cluster initiatives in education system"; caring out in Silesian University of Technology; financed by Ministry of Science and Higher Education; no 0193/B/H03/2010/39). The paper presents good practices in vocational education to implement in the initiative and a map of categories of solution. Research also indicated barriers and abilities of the implementation those solutions (or elements of them). The proposal to adapt the education to labour market requirements is based on integrated research and monitoring on cluster initiative's participants. They are: pupils, educational area (mainly: schools directors and teachers), employers and local governments. The paper also highlights the model of cluster initiative in education. Research helped to indicate areas of the best climate to create cluster initiative, barriers and difficulties, ways of communication, range of corporation in the initiative. Indicated operations, processes and role of participants in cluster initiative will help to create the expert system to support educational management in conjunction with labour market needs. The idea of expert system is to activate communication between potential participant in cluster initiative. Making decisions on the basis of scientific research will make them rational. A tool used by every participant will help to create cluster initiative in education (firstly very narrow) and to support functioning of the cluster initiative.
Keywords: 330